Cordycepin Inhibits the Growth of Hepatocellular Carcinoma by Regulating the Pathway of Aerobic Glycolysis. (23rd November 2022) - Chen, Ya; Jiang, Yuan; Huang, Xinyu; Chen, Lin; Yang, Hao; Zhao, Jian; Liang, Beibei
Abstract : Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in China, with a high incidence and mortality rate. Glucose metabolism reprogramming is a major characteristic of tumor cells. Increasing evidence indicates that aerobic glycolysis is associated with tumor growth and insensitivity to chemotherapy. Cordycepin inhibits the growth of HCC cells, but the mechanism is yet to be elucidated. Herein, in vitro and in vivo methods were utilized to investigate the cordycepin-inhibited growth of HCC by regulating the metabolic pathway of aerobic glycolysis. In vitro analyses using colony formation and flow cytometry revealed that cordycepin inhibits HCC cells' proliferation and promotes apoptosis. In addition, cordycepin reduced the production of lactic acid and pyruvate, reduced the uptake of glucose, and decreased the extracellular acidification in HCC cells. Specifically, cordycepin inhibited the expression of HK2, LDHA, and PKM2 in aerobic glycolysis via the AMPK-Akt pathway. Taken together, these findings revealed that cordycepin reduces the tumor energy supply and decreases lactic acid production, thereby inhibiting the growth of HCC cells by regulating the metabolic pathway of aerobic glycolysis. These findings might provide novel insights into the mechanisms underlying cordycepin-mediated inhibition of tumor growth as well as a new treatment for HCC.